The Copy Effect in Translation: On Formal Similarity and the Book Historic Perspective - Fraser, Ryan (TTR)

(untitled) (Association canadienne de traductologie, 2020)
This study takes up the perspective of material book history to revisit the paradox of identity and difference that has always been central to translation. I will argue here that a cognitive effect of identity in translation—which I am calling the “copy effect”—remains to be grappled with theoretically in its own right, and that contemporary theory has generally used the idea of “identity” in translation as a mute antithesis from which to repel with discourse privileging variance and difference. My goal here is to talk about the identity inherent in any translation, and the powerful effect of formal identity that a good number of translations display. First, I will address the paradox itself. Then I will draw attention to the material side of the verbal and linguistic and make a sharp distinction between two types of “form” that textual discourse can take: (1) a “stylistic form” that is qualitative and that translators feel free to vary; and (2) a “Pythagorean form” that is primarily quantitative and derived from textual materiality, and that translators tend to map over with a stricter attention to invariance. Translation scholars, we will see, have been reluctant to distinguish between these two types of form, which has resulted in denials and elisions conflicting with the material evidence of translation. Then I will pursue this material perspective on translation and seek out discourse situating a “copy effect” historically and culturally. This will lead to a discussion of Rita Copeland’s connection between translation and the classical and medieval copia verborum. Finally, I will enter into a new line of reflection opened by Anthony Pym, and propose that through the copia verborum and its historic and contemporary use in construing literalist translations, a compelling analogy can be drawn between medieval translation practices and modern-day digital ones using translation memories.